Development of a maximal testing protocol for the NordicTrack cross-country ski simulator - Haug, R. C.; Porcari, J. P.; Brice, G.; Terry, L. (Medicine & Science in Sports & Exercise, 1999)
The testing protocol developed for the NT XC simulator is valid and can be expected to elicit similar maximal values when compared with maximal graded treadmill (TM) testing.